Phosphorus concentrations in sequentially fractionated soil samples as affected by digestion methods - Do Nascimento C.A.C. (2015)
Sequential fractionation has helped improving our understanding of the lability and bioavailability of P in soil. Nevertheless, there have been no reports on how manipulation of the different fractions prior to analyses affects the total P (TP) concentrations measured. This study investigated the effects of sample digestion, filtration, and acidification on the TP concentrations determined by ICP-OES in 20 soil samples. Total P in extracts were either determined without digestion by ICP-OES, or ICP-OES following block digestion, or autoclave digestion. The effects of sample filtration, and acidification on undigested alkaline extracts prior to ICP-OES were also evaluated. Results showed that, TP concentrations were greatest in the block-digested extracts, though the variability introduced by the block-digestion was the highest. Acidification of NaHCO 3 extracts resulted in lower TP concentrations, while acidification of NaOH randomly increased or decreased TP concentrations. The precision observed with ICP-OES of undigested extracts suggests this should be the preferred method for TP determination in sequentially extracted samples. Thus, observations reported in this work would be helpful in appropriate sample handling for P determination, thereby improving the precision of P determination. The results are also useful for literature data comparison and discussion when there are differences in sample treatments.